Stress Coping Strategies Among Nurses at Hasanuddin University Hospital Indonesia - Adelia U. Ady Mangilep; Noer Bahry Noor; Rini Anggraeni; Adelia L F Sinaga (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Nurses have a major contribution in determining the quality of hospital services, but the heavy workload carried by nurses makes them vulnerable to work stress. Work stress that is if not handled properly can result in a decrease in the quality of services provided to the effect on hospital productivity, therefore it is necessary to do a coping strategy so that nurses can deal with and neutralize or overcomereduce the work stress experienced. Objective: This study aims to describe stress coping strategies for nurses in the Inpatient Installation of the Hasanuddin University Hospital Makassar. Method: This research was using quantitative approach. It was conducted at the Hasanuddin University Hospital in July 2022. The population in this study were all nurses who served in the Inpatient Room of Hasanuddin University Hospital with a total sample of 54 nurses. Collecting research data using The Brief COPE Questionnaire. The data were analyzed by using univariate analysis test. Result: The results describe nurses' stress coping strategies based on problem focused coping, that all indicators included in the high category, there are active coping (6.42), followed by planning (6.29) and use of instrumental support (6.02). Then the Nnurse's stress coping strategy based on emotional focused coping, there are 3 indicators that are included in the high category, there are religion (7.39), positive reframing (6.31), and acceptance (6.07), use of emotional support (4 .83) is an indicator that included in the medium category and denial (3.14) is an indicator that included in the low category. While Nnurses' stress coping strategies based on dysfunctional coping, self-distraction (6,16) is the only indicators that included in the high category, then there are 4 indicators that were included in the moderate category, there were namely venting (4,87), humor (4,50), self blame (4.50), and behavioral disengagement (3.24), as well as substance use (2.66) are indicators that are included in the low category. Conclusion: Majority of nurses at Hasanuddin University Hospital applied high problem focused coping and emotional focused coping. Therefore, the management of the Hasanuddin University Hospital may consider opening or holding a communication forum between nurses in each treatment room to discuss problems at work and provide psychological guidance and support in order to overcome the work stress that nurses experienced.